A new species of Woodcock (Aves: Scolopacidae: Scolopax) from Hispaniola, West Indies - Takano, Oona M.; Steadman, David W. (Zootaxa, 2015)
Several hundred late Holocene fossils from Trouing Jean Paul, a cave in Massif de la Selle, Haiti, represent an extinct species of woodcock (Scolopax brachycarpa, new species). Scolopax brachycarpa is known from most major skeletal elements; although volant, its carpometacarpus was very short relative to its humerus. The only other species of Scolopax from the West Indies is the extinct and presumably closely related S. anthonyi of Puerto Rico, which also had a relatively short carpometacarpus compared to continental congeners. Both Scolopax brachycarpa and S. anthonyi share more osteological characters with the Eurasian S. rusticola than with the North American S. minor.